Visibility, Precarity and Public Spaces: Reading Matthew Arnold’s “West London” in an Indian Classroom - Bhattacharya, Saradindu (Radical Teacher, 2024)
This essay is an account of my experience of teaching Matthew Arnold's "West London" in an Indian classroom through the conceptual prism of vulnerability. The essay argues that the configuration of public space in Arnold's poem in terms of differential class relations in Victorian society offers a literary mode of visualizing vulnerablity and prompts an ethical recognition of the humanness of marginalized characters. It further demonstrates how the peadgogic exercise of 'reading' such poetry in the contemporary urban Indian context can alert students to the politics of occupying and negotiating public spaces in terms of (the lack of) class position and privilege across diverse cultural and historical contexts.